If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7 = 3(x + y) Reorder the terms: -7 + 5x = 3(x + y) -7 + 5x = (x * 3 + y * 3) -7 + 5x = (3x + 3y) Solving -7 + 5x = 3x + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -7 + 5x + -3x = 3x + -3x + 3y Combine like terms: 5x + -3x = 2x -7 + 2x = 3x + -3x + 3y Combine like terms: 3x + -3x = 0 -7 + 2x = 0 + 3y -7 + 2x = 3y Add '7' to each side of the equation. -7 + 7 + 2x = 7 + 3y Combine like terms: -7 + 7 = 0 0 + 2x = 7 + 3y 2x = 7 + 3y Divide each side by '2'. x = 3.5 + 1.5y Simplifying x = 3.5 + 1.5y
| 6x+8y=140 | | -5c+4(2c+7)=-43 | | 4x^2+16-32=0 | | -(-x+3)= | | [4(x+5)-8]-[3-4(x-2)]= | | 4=-8v+4(v+5) | | -5-3x-7x=-85 | | 6[1-(-3x-9)]=90x+276 | | 45=3(4+y) | | 0.5y+0.9(y+4)=0.3(12) | | 21-7v=6(3-v) | | 7.5n-4(-3-6.4n)=20+37.1 | | 5m-7n+8m-8n= | | 14x+.11y=.124 | | -3(x+2)=-19.5 | | 9-2k=3 | | 7+6x=-1 | | 0=1a-2 | | 3x+4(-5x-5)=-207 | | P=450+.03+3 | | 1y+-6=4 | | 6x+4y=-15 | | 10/1-2/3=x | | 36x^2-12h+1=0 | | 0=9a-2 | | 8(2n+2)=9(9n+5)+3 | | 22x^9-2x^3= | | Y=2(3.14)x | | -2(n-4)=4(3-2) | | ax+3=8a+b | | 2=5f-3 | | (x+2)(x+3)=x^2+5x+q |